New taxa of the tribe Apomecynini (Coleoptera: Cerambycidae: Lamiinae) from Mexico - Noguera, Felipe Arturo; Gutiérrez-Trejo, Nayeli; Toledo-Hernández, Víctor Hugo; Santos-Silva, Antonio (Zootaxa, 2026)
Four new taxa of the tribe Apomecynini are described from Mexico: Apomystirio gen. nov. and Apomystirio hispidum sp. nov. from the state of Chiapas; Adetaptera ignota sp. nov. from the state of Chiapas; and Adetus lunaris sp. nov. from the state of Jalisco.